DASHBOARD SUSTAINABLE DEVELOPMENT GOALS (SDGS) MENGGUNAKAN FRAMEWORK LARAVEL (STUDI KASUS KABUPATEN DAN KOTA PROVINSI LAMPUNG) - Tristiyanto Tristiyanto; Yunda Heningtyas; Aristoteles Aristoteles; Muhammad Yusuf Amran (Jurnal Pepadun, 2021)
On March 18, 1964, the Province of Lampung was established. In order to carry out efforts to develop Lampung Province, a development framework with a legal foundation and justice in each development process is required. The Sustainable Development Goals (SDGs) are a replacement for the Millennium Development Goals (MDGs), which were established as a result of an agreement amongst 189 leaders of UN member states with the primary goal of improving welfare and community development. As a result of this research, a dashboard was established to track the progress of the SDG indicators. The dashboard produced can analyze, manage, and display the progress of the SDG indicators in a way that all parties can simply read and understand. As a result, everyone at every level of society can understand and guarantee that development is carried out in accordance with the law in order to promote community welfare.